Ethical analysis of informed consent methods in longitudinal cohort studies: A Chinese perspective - Li, Kun; Huang, Mingtao; Zhai, Xiaomei; Wang, Chen (Developing world bioethics, 2025)
In longitudinal cohort studies involving large populations over extended periods, informed consent entails numerous urgent challenges. This paper explores challenges regarding informed consent in long‐term, large‐scale longitudinal cohort studies based on the longitudinal and dynamic nature of such research. It analyzes and evaluates widely recognized broad consent and dynamic consent methods, highlighting limitations concerning their ability to adapt to evolving research objectives and participant perspectives. This paper discusses trust‐based informed consent and emphasizes the needs to establish and maintain trust with research participants and to balance information disclosure with respect for participants' autonomy. Informed consent in long‐term studies is an evolving process that must adapt to changing research environments. Based on participant trust, researchers should observe and assess potential research risks. Finally, the paper recommends enhancing institutional credibility, implementing reconsent procedures, and ensuring robust ethical oversight to safeguard participants' rights despite the complexity of modern biomedical research.